Comparing the outcomes of early and late acquisition of european portuguese: an analysis of morpho-syntactic and phonetic performance - Flores, Cristina (2017)
The present paper compares the linguistic competence of German-Portuguese bilinguals with upper-intermediate German L2 learners (L2ers) of EP (European Portuguese) and with monolingual Portuguese speakers. The bilingual speakers are heritage speakers (HSs), who were raised bilingually with EP as the minority language and German as the majority language. The aim of our comparison is to verify in which way different input sources and maturational effects shape the speakers’ linguistic knowledge. The findings of two studies, one focused on the morpho-syntactic knowledge of clitics and the other on global accent, corroborate the assumption that L2ers and HSs behave differently, despite superficial similarities observed in the morpho-syntactic study. In contrast to that of the L2ers’, the accent of the HSs is perceived as being native-like, whereas their morpho-syntactic competence is mainly shaped by their dominant exposure to colloquial Portuguese and reduced contact with formal registers.